Activation of macrophages by food antigens: enhancing effect of gluten on nitric oxide and cytokine production - Tucková, L; Flegelová, Z; Tlaskalová-Hogenová, H; Zídek, Z (Journal of leukocyte biology, 2000)
Macrophages play an important role in effector mechanisms of various chronic inflammatory diseases. We studied the effect of gluten, the agent inducing celiac disease, and other food antigens on the activation of macrophages. Nitric oxide (NO) and cytokine production were followed as markers of activation, using cultured murine peritoneal macrophages. None of the food antigens tested caused direct inducible nitric oxide synthase (iNOS) activation in macrophages. Unlike other food antigens gluten, gliadin, and their proteolytic fragments significantly enhanced NO production when applied together with interferon-gamma (IFN-gamma), the most efficient being fragments originating from 25- to 45-min peptic digestion. The activation pathway was mediated via direct stimulation of tumor necrosis factor alpha (TNF-alpha) secretion. The NO-enhancing effect was confirmed at the level of iNOS mRNA transcription. In case of sustained local inflammatory reaction connected with increase of IFN-gamma, gluten and its proteolytic fragments may thus elevate NO production. Increased NO level could consequently participate in the development of mucosal lesions in the gut of celiac patients.
Keywords: Nitric Oxide Synthase Type II; peritoneální makrofágy; antigeny; messenger RNA; cytokiny; Nitrites; Female; Macrophage Activation; Interleukin-10; oxid dusnatý; myši inbrední C3H; Glutens; synthasa oxidu dusnatého; myši inbrední BALB C; Antigens; Mice, Inbred C3H; zvířata; Nitric Oxide; myši; Cells, Cultured; dusitany; Macrophages, Peritoneal; Mice; TNF-alfa; Peptide Fragments; Transcriptional Activation; aktivace transkripce; RNA, Messenger; gliadin; ženské pohlaví; aktivace makrofágů; synthasa oxidu dusnatého, typ II; kultivované buňky; Gliadin; Cytokines; peptidové fragmenty; interferon gama; Tumor Necrosis Factor-alpha; gluteny; interleukin-10; Animals; Food; potraviny; Nitric Oxide Synthase; Mice, Inbred BALB C; Interferon-gamma